2005
DOI: 10.1074/jbc.m500577200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for the Complex Binding Specificity of the PDZ Domain in PICK1

Abstract: PICK1 (protein interacting with C kinase 1) contains a single PDZ domain known to mediate interaction with the C termini of several receptors, transporters, ion channels, and kinases. In contrast to most PDZ domains, the PICK1 PDZ domain interacts with binding sequences classifiable as type I (terminating in (S/T)X⌽; X, any residue) as well as type II (⌽X⌽; ⌽, any hydrophobic residue). To enable direct assessment of the affinity of the PICK1 PDZ domain for its binding partners we developed a purification schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
143
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(161 citation statements)
references
References 53 publications
12
143
2
Order By: Relevance
“…On the other hand, docking Class II peptide to of Cipp-PDZ9 using our flexible approach gives consistently lower RMSD of 0.23 Å . As observed in earlier PDZ docking cases, the inclusion of backbone flexibility through ENM-REMD snapshots does a better job in discriminating that that Lrcc7 has affinity towards Class I peptide, and [87][88][89] Yet, there are several mutations that have been reported previously, such as the mutation of lysine 27 (K27E) to glutamic acid alone or together with aspartic acid 28 (D28A) to alanine, which completely disrupt the interaction with both GluR2 and PKCa. 89 Moreover, the experimental study of Dev et al 87 has shown that mutating lysine 27 to glutamic acid, a point mutation on the bA-bB loop, changes the binding selectivity of PICK1 to exhibit only Class I behavior.…”
Section: Flexible Docking For Homolog and Mutant Structuresmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, docking Class II peptide to of Cipp-PDZ9 using our flexible approach gives consistently lower RMSD of 0.23 Å . As observed in earlier PDZ docking cases, the inclusion of backbone flexibility through ENM-REMD snapshots does a better job in discriminating that that Lrcc7 has affinity towards Class I peptide, and [87][88][89] Yet, there are several mutations that have been reported previously, such as the mutation of lysine 27 (K27E) to glutamic acid alone or together with aspartic acid 28 (D28A) to alanine, which completely disrupt the interaction with both GluR2 and PKCa. 89 Moreover, the experimental study of Dev et al 87 has shown that mutating lysine 27 to glutamic acid, a point mutation on the bA-bB loop, changes the binding selectivity of PICK1 to exhibit only Class I behavior.…”
Section: Flexible Docking For Homolog and Mutant Structuresmentioning
confidence: 78%
“…89 Moreover, the experimental study of Dev et al 87 has shown that mutating lysine 27 to glutamic acid, a point mutation on the bA-bB loop, changes the binding selectivity of PICK1 to exhibit only Class I behavior. Another mutation study that replaces the residue in aB helix (lysine 83 to histidine) by Madsen et al 88 showed that the preference of PICK1 reverts to that of a Class I motif. Docking Class I and Class II peptides to the unbound conformation of wild and mutant PICK1 does not show the change in selectivity upon mutation [brown and red dots in the Figure 4(A-C)].…”
Section: Flexible Docking For Homolog and Mutant Structuresmentioning
confidence: 99%
“…Through its single PDZ domain, PICK1 binds numerous synaptic proteins, including several neurotransmitter receptors, transporters, and ion channels (Madsen et al, 2005). Furthermore, PICK1 can dimerize via its central coiled-coil motif and thereby promote protein complex formation between its binding partners.…”
Section: Parkin Suppresses Pick1-mediated Potentiation Of Asic2a Currmentioning
confidence: 99%
“…PICK1 is a synaptic scaffolding protein known to functionally interact with an assortment of neurotransmitter receptors, transporters, and ion channels (Madsen et al, 2005). Unlike CASK, however, PICK1 is a substrate for parkin-mediated ubiquitination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation